Congress of Neurological Surgeons Systematic Review and Evidence-Based Guidelines for Perioperative Spine: Preoperative Surgical Risk Assessment. (7th September 2021) - Harrop, James S; Mohamed, Basma; Bisson, Erica F; Dhall, Sanjay; Dimar, John; Mummaneni, Praveen V; Wang, Marjorie C; Hoh, Daniel J
Abstract: BACKGROUND: Patient factors (increased body mass index [BMI], smoking, and diabetes) may impact outcomes after spine surgery. There is a lack of consensus regarding which factors should be screened for and potentially modified preoperatively to optimize outcome. OBJECTIVE: The purpose of this evidence-based clinical practice guideline is to determine if preoperative patient factors of diabetes, smoking, and increased BMI impact surgical outcomes. METHODS: A systematic review of the literature for studies relevant to spine surgery was performed using the National Library of Medicine PubMed database and the Cochrane Library. Clinical studies evaluating the impact of diabetes or increased BMI with reoperation and/or surgical site infection (SSI) were selected for review. In addition, the impact of preoperative smoking on patients undergoing spinal fusion was reviewed. RESULTS: A total of 699 articles met inclusion criteria and 64 were included in the systematic review. In patients with diabetes, a preoperative hemoglobin A1c (HbA1c ) >7.5 mg/dL is associated with an increased risk of reoperation or infection after spine surgery. The review noted conflicting studies regarding the relationship between increased BMI and SSI or reoperation. Preoperative smoking is associated with increased risk of reoperation (Grade B). There is insufficient evidence that cessation of smoking before spine surgery decreases the risk of reoperation. CONCLUSION: This evidence-based guideline provides a Grade B recommendation that diabetic individuals undergoing spine surgery should have a preoperative HbA1c test before surgery and should be counseled regarding the increased risk of reoperation or infection if the level is >7.5 mg/dL. There is conflicting evidence that BMI correlates with greater SSI rate or reoperation rate (Grade I). Smoking is associated with increased risk of reoperation (Grade B) in patients undergoing spinal fusion. The full guidelines can be accessed at https://www.cns.org/guidelines/browse-guidelines-detail/2-preoperative-surgical-risk-assessement